Decision Support System for Selecting Order Types Using the SAW-AHP Method - M Mahaputra Hidayat; Mas Nurul Hamidah; Rizky Wahyu Prastyawan (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
This study aims to make it easier for users to choose the type of orchid that is suitable for planting in the user's environmental conditions. This research was conducted because there were many orchid enthusiasts who wanted to cultivate it but it was not balanced with knowledge of the characteristics of orchids that can live in ideal environmental conditions. The SAW method plays a role in the initial classification where the results of the SAW method classification are sorted from the largest value to the smallest value, then the 10 best results from the SAW method will be processed by the AHP method and produce the final result, the recommended orchid. The final result obtained in this system is in accordance with the manual calculations performed, this means that the system classifies rules properly and accordingly.